Respuesta :

Step-by-step explanation:

Lets assume that x=0

Therefore- 2×0-y= -3

                0 - y =-3

Therefore y = -3

Then lets take now the before equation

2x - 3= -3

2x = -3+3

2x=0

x=0÷2

∴ x= 0

Answer is- 0,-3

See image

You have to change the equation so it's in the form y=mx+b.

b is the y-intercept and it is a good starting point and m is the slope and it tells you directions to the next point (also how steep or flat and if it's going up or down) See image

Ver imagen lpina68
ACCESS MORE